SISTEM PEMASARAN GAMBIR DI SUMATERA BARAT (Kasus di Kecamatan Kapur IX, Kabupaten Lima Puluh Kota) - Amelira Haris Nasution; Ratna Winandi Asmarantaka; Luqman M Baga (Universitas Sebelas Maret, 2015)
Gambier is one of the commodity export in Indonesia and it has been supplied 80% of the world’s needs. The largest gambier production area is Lima Puluh Kota Regency, West Sumatera (70,39%). The benefit from its position as the biggest gambier supplier or producer is not enjoyed by gambier farmer because of weak gambier marketing and the role of merchand middlement had a more powerful and dominant for determine of gambier prices. The purpose of this study is analyzing marketing system of gambier through marketing channel analysis, marketing channel’s role analysis (farmer group and merchand middlemen) and operational efficiency analysis. This study was conducted from Desember 2014 until January 2015 in Kapur IX Subdistrict, Lima Puluh Kota Regency, West Sumatera. Farmer s were chosen by purposive sampling method and middlemen were chosen by snowball sampling method. Data processing in this study was using descriptive qualitative and quantitative analysis. The result of this study showed that there are 4 marketing channels of gambier marketing. Based on operational efficiency indicator, all marketing channels had been inefficiency because of weak farmer’s bargaining power so their role is just as a price taker. But among all marketing channels, channel 4 is more efficient relatively based on benefit and cost ratio, price share and marketing function implementation. The result of this study also showed that farmer group and farmer association of gambier are still in starter institution so that they are not capable to contribute in marketing gambier.